Pharmacokinetic analysis of new synthetic antimalarial N-251 - Kazuaki Okada; Akira Sato; Akiko Hiramoto; Rena Isogawa; Yuji Kurosaki; Kazutaka Higaki; Shin-Ichi Miyoshi; Kyung-Soo Chang; Hye-Sook Kim (Tropical Medicine and Health, 2019)
Abstract Background With the emergence and growing number of drug-resistant Plasmodium falciparum, a new drug for malaria control must be urgently developed. The new antimalarial synthetic compound N-251 was recently discovered. As an endoperoxide structure in the body, the compound shows high antimalarial activity and curative effects. We performed a pharmacokinetic (PK) analysis of N-251 under various conditions using mice to understand the inhibitory effect of N-251 in parasite-infected mice. Results PK study of N-251 after intravenous and oral administration in mice showed plasma concentration of N-251 was decreased drastically by intravenous route. C max was reached in 2 h after oral administration of N-251, and the level decreased to a level similar to that obtained after intravenous administration. The area under the curves (AUCs) of the plasma concentration of N-251 increased dose-proportionally in both administrations, and bioavailability (F) was approximately 23%. Additionally, T max, C max, AUC, and F increased in fasted mice compared to normal-fed mice after the administration of N-251, indicating the influence of diet on the absorption kinetics of N-251. Furthermore, in parasite-infected fasted mice, the plasma concentration-time profile of N-251 was similar to that in normal-fasted mice. Based on the PK parameters of single oral administration of N-251, we investigated the effect of multiple oral doses of N-251 (68 mg/kg three times per day for 2 days) in normal-fed mice. The plasma concentration of N-251 was between 10 and 1000 ng/mL. The simulation curve calculated based on the PK parameters obtained from the single-dose study well described the plasma concentrations after multiple oral dosing, indicating that N-251 did not accumulate in the mice. Multiple oral administrations of N-251 in mice were required to completely eliminate parasites without accumulation of N-251. Conclusions N-251 has been selected as a potent antimalarial candidate. We found that N-251 showed short half-life in plasma, and AUCs increased proportionally to dose. With multiple doses of N-251, the plasma level of N-251 was greater than 10 ng/mL in normal-fed mice, and accumulation of N-251 was not observed; however, multiple treatments with N-251 are required for the complete cure of parasite-infected mice. Determining the appropriate dosage was an important step in the clinical applications of N-251.